La sostenibilidad financiera de los gobiernos autónomos descentralizados municipales frente a las demandas de inversión, enfocada al GAD municipal de Las Lajas periodo 2019-2020. - Ordoñez Castillo, Veronica Paulett (2022)
This research work is focused on the study of financial sustainability of decentralized autonomous governments in terms of investment demands, in order to know in detail, the activities that these institutions must perform to obtain the necessary economic resources and operate successfully. The main goal of this work is to propose a financing model that allows the municipal GAD of Las Lajas to fulfill and improve the services and needs of the community, due to a lack of clear strategies and an appropriate financing model, since the only incomes come from taxes, fees, contributions, and budget allocated by the State. The methodology used in this work allowed us to examine the process of targeting investment demands through municipal planning instruments, which— for this research—is the Territorial Development and Land-use Plan of the Municipal GAD of Las Lajas, a semi-structured interview was also conducted to the directors of the institution, and a financial diagnosis that allowed to know the situation of the Municipal GAD of Las Lajas. This study concluded that the most appropriate financing model to be applied in the municipal GAD of Las Lajas corresponds to the financing model through non-refundable international cooperation. Thus, an operational plan that includes several strategies was designed. This plan has a high level of applicability according to the requirements of the Municipality and the population.